Knowledge and attitudes toward human papillomavirus and cervical cancer prevention among women in the Asir Region, Saudi Arabia: a cross-sectional study - Kandasamy, Geetha; Orayj, Khalid; Shorog, Eman; Alshahrani, Asma M.; Alanazi, Tahani S.; Algorman, Hanan S. (Frontiers in Oncology, 2025)
BackgroundCervical cancer, mainly caused by Human Papillomavirus infection, is a growing public health concern in Saudi Arabia. Despite the availability of effective vaccination and screening programs in the country, awareness and acceptance remain limited, particularly among women in the Asir region. This study aimed to assess knowledge and attitudes toward Human Papillomavirus and cervical cancer prevention among women in the Asir region, Saudi Arabia.MethodsA cross-sectional study was conducted from January to March 2025 among women aged 18 and older in the Asir region of Saudi Arabia. A convenience sampling method was used to recruit participants. Data were collected through an online self-administered questionnaire, and multivariable logistic regression was performed to identify factors associated with knowledge and attitudes (p < 0.05).ResultsAmong the 523 participants, 66% demonstrated good knowledge of Human Papillomavirus and cervical cancer prevention, while 56% had positive attitudes. Awareness of Human Papillomavirus and the Human Papillomavirus vaccine was observed in 62.1% and 54% of women, respectively, while knowledge of screening tests remained limited at 32.7%. Only 21% of women reported being vaccinated against Human Papillomavirus. The main barriers discouraging women from practicing Pap tests were discomfort (65.4%) and lack of knowledge (63.7%). Factors significantly associated with lower odds of having good knowledge (Adjusted Odds Ratio, AOR) included older age (41–50 years: AOR = 0.479, 95% confidence interval (CI): 0.239–0.961; 51–60 years: AOR = 0.239, 95% CI: 0.113–0.505; >60 years: AOR = 0.127, 95% CI: 0.022–0.724), lower education (secondary school: AOR = 0.483, 95% CI: 0.305–0.764), and unmarried status (single: AOR = 0.562, 95% CI: 0.327–0.965; divorced/widowed: AOR = 0.413, 95% CI: 0.218–0.784). Negative attitudes were more prevalent among older women (41–50 years: AOR = 0.327, 95% CI: 0.170–0.629; 51–60 years: AOR = 0.272, 95% CI: 0.130–0.570; >60 years: AOR = 0.102, 95% CI: 0.012–0.876).ConclusionThe study demonstrated generally good knowledge and positive attitudes toward Human Papillomavirus vaccination and cervical cancer prevention among women in the Asir region; however, awareness of screening and vaccine uptake was suboptimal. Women who were older, less educated, or unmarried had lower knowledge and more negative attitudes. Targeted educational interventions through healthcare providers, school-based programs, and social media, along with improved healthcare access, are recommended to enhance awareness, encourage regular cervical cancer screening, and reduce disease burden.